PENGEMBANGAN MEDIA PEMBELAJARAN TEKS CERITA PENDEK DENGAN VIDEO SLIDE SHOW - Lenny Rahmawati; Munaris Munaris; Bambang Riadi (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2020)
This study aims to determine the development of short story text learning media with Video Slide show. The method used in this research is Research and Development (RD). The results of this research and development are multimedia learning tools in the form of CDs containing doc and mp4 that have been declared fit for use by media experts, material experts, and Indonesian language teachers as learning resources and learning aids. The validity of the material experts obtained an average score of 3.00, and the average percentage of 71.36% with a decent category. The results of the validation of media experts obtained an average score of 3.21, and a percentage of 80.25 with a very decent category. The results of the validation of Indonesian language teachers obtained an average score of 3.77, and the average percentage of 94.34% with a very decent category. Penelitian ini bertujuan mengetahui pengembangan media pembelajaran  teks cerpen dengan Video Slide show. Metode yang digunakan dalam penelitian ini adalah Research and Development (RD). Hasil  penelitian  dan pengembangan  ini  adalah perangkat  multimedia pembelajaran dalam bentuk CD yang berisi doc dan mp4 yang telah dinyatakan layak digunakan oleh ahli media, ahli materi, dan guru bahasa Indonesia sebagai sumber belajar dan alat bantu pembelajaran.  Validitas ahli materi diperoleh skor rata-rata 3,00, dan rerata presentase 71,36% dengan kategori layak. Hasil validasi ahli media diperoleh skor rata-rata 3,21, dan retata presentase 80,25 dengan kategori sangat layak. Hasil validasi guru bahasa Indonesia diperoleh skor rata-rata 3,77, dan rerata presentase 94,34% dengan kategori sangat layak. Keywords: media, research and development, and validity